Pengembangan Video Assignment Based on Motion Analysis (Vabma) Pada Pembelajaran Senam Lantai - Rama Adha Septiana; Dedi Kurnia; Gita Febria Friskawati (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The assignment of Physical Education teaching learning material when virtual learning in this new normal era for elementary school (SD) students is very important, especially on the front roll material. The reason is, the front roll material cannot be done without understanding the movements thoroughly. When students misunderstand it, there is a big chance of injury. Thereforethe development of assignment media in learning front roll is needed. The purpose of this study was to develop the assignment of exercise material using Video assignment Based on Motion Analysis (VABMA) for elementary school students. This study used the analytical design development implementation evaluation (ADDIE) methodThe test results from specialists on the subject of the material and media serveas the study's primary source of data. Percentage analysis is used in data analysis to determine the viability of this assignment medium. The findings revealed that. Data analysis uses percentage analysis to see whether or not the media for this assignment is feasible. The results showed that the VABMA media was feasible to use in assignments to floor exercise material for elementary school students.